From Family Herbal Plants to Interaction Place: Enhancing Community Engagement in RW 05, Palmerah Urban Kampong - Anggiani, Mona; Artiningrum, Primi; Lelo, Lelo; Arroyan, M. Iqbal; Ismail, Ahmad (Universitas Mercu Buana, 2025)
Taman Cempaka in Palmerah Urban Kampongs has the potential to be developed as a family medicinal plant (toga) garden as well as a social interaction space. This activity found that the number and variety of herbal medicinal plants increased, the park management system was better with digital technology, and the quality of the social interaction space improved. The UMB team identified two main challenges: the limited variety and quantity of medicinal plants and the suboptimal management of harvested produce. These issues were also confirmed by project partners. This project aims to enhance the function of the Taman Toga as both a green space and a social hub, improve its overall quality, and provide digital training for its managers. The methods used include planting, rearranging, management, and socialization. This program also includes technology training and the use of online platforms for marketing herbal plant products. The project stages include initial meetings, socialization, problem identification, solution implementation, digital system implementation, and monitoring and evaluation. The results showed an increase in the number and variety of toga plants and an increase in the use of the park as a community interaction space. Overall, this project succeeded in enriching the diversity of medicinal plants, improving digital park management, and improving the quality of the social interaction space. In addition, this activity has a positive impact on the environment by making the park more beautiful, comfortable, and functional for the surrounding community.